2019
DOI: 10.3389/fped.2019.00224
|View full text |Cite
|
Sign up to set email alerts
|

Mother's Own Milk and Bronchopulmonary Dysplasia: A Systematic Review and Meta-Analysis

Abstract: Background: Bronchopulmonary dysplasia (BPD) is the most common complication of very preterm birth and can lead to lifelong health consequences. Optimal nutrition is a cornerstone in the prevention and treatment of BPD. In very preterm infants, mother's own milk (MOM) feeding is associated with lower risks of necrotizing enterocolitis, retinopathy of prematurity, and sepsis. Although several studies have shown that MOM may protect against BPD, a systematic analysis of the evidence has not been perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 59 publications
1
42
0
1
Order By: Relevance
“…Human milk feeding decreases the risk of NEC (28). Meta-analyses suggest a benefit in feeding mother's own milk (29) and pasteurized donor human milk (30) in the prevention of BPD. In organoids derived from the terminal ileum of mouse pups, human milk exosomes have been shown to attenuate LPS induced activation of TLR4 (31).…”
Section: Discussionmentioning
confidence: 99%
“…Human milk feeding decreases the risk of NEC (28). Meta-analyses suggest a benefit in feeding mother's own milk (29) and pasteurized donor human milk (30) in the prevention of BPD. In organoids derived from the terminal ileum of mouse pups, human milk exosomes have been shown to attenuate LPS induced activation of TLR4 (31).…”
Section: Discussionmentioning
confidence: 99%
“…Breast milk supply increases microbial diversity and enhances immunologic properties while antibiotic therapy is a major cause of microbial dysbiosis. In the context of lung development and lung injury, meta-analyses of breast milk supply display a relevant reduction in the incidence of BPD [ 21 , 22 ]. Furthermore, recent studies demonstrated that antibiotic therapy per se and its prolonged use was associated with an increased risk for BPD [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, data suggesting a bene cial impact of maternal milk feeding on BPD were limited. Some investigators had concluded that maternal milk decreased incidence of BPD [7,[11][12][13][14], but others had not thought it useful [15]. Thus we can make two postulations: either high-volume maternal milk feeding daily directly impacts BPD or BPD has an obvious effect on volume maternal milk feeding .…”
Section: Discussionmentioning
confidence: 99%